Impact and safety of endoscopic ultrasound guided fine needle aspiration on patients with cirrhosis and pyrexia of unknown origin in India - Choudhary, Narendra; Bansal, Rinkesh Kumar; Puri, Rajesh; Singh, Rajiv Ranjan; Nasa, Mukesh; Shah, Vinit; Sarin, Haimanti; Guleria, Mridula; Saigal, Sanjiv; Saraf, Neeraj; Sud, Randhir; Soin, Arvinder S. (Endoscopy International Open, 2016)
Background and aims: Etiologic diagnosis of pyrexia of unknown origin is important in patients with cirrhosis for optimal management and to prevent flare up of infectious disease after liver transplantation. However, there is very limited literature available on this subject. The present study aimed to examine the safety and impact of endoscopic ultrasound (EUS) guided fine needle aspiration (FNA) in patients with cirrhosis.Methods: The study was conducted between January 2014 and January 2016 at a tertiary care center. A total of 50 (47 lymph nodes, 3 adrenal) EUS guided FNAs were performed in 46 patients. Data are presented as median (25 – 75 IQR).Results: The study included 46 patients (40 males) whose mean age was 47.9 ± 11.1 (SD) years; mean Child-Turcotte-Pugh (CTP) score and mean MELD (Model for End-Stage Liver Disease) score were 10 (8 – 11) and 18 (12 – 20), respectively. The Child Pugh class was A in 4, B in 14, and C in 28 (including three patients with adrenal FNAs). Indications for FNA were pyrexia of unknown origin and lymphadenopathy on CT imaging. The cytopathological diagnoses were metastatic disease in 1 (adrenal), granulomatous change in 10 (6 positive with acid fast bacilli stain), histoplasmosis in three (two adrenals, one lymph node), 32 lymph nodes were reactive and four lymph node FNAs showed inadequate cellularity. The pathologic nodes had significantly lower long-to-short axis ratio [1.25 (1.09 – 1.28) versus 1.46 (1.22 – 1.87), P = 0.020]; a higher proportion of hypoechoic echotexture (5 versus 3, P = 0.017), and sharply defined borders (4 versus 2, P = 0.029). Complications included mild hepatic encephalopathy related to sedation in two patients with Child’s C status.Conclusion: EUS guided FNA is safe in patients with cirrhosis and modified the management in 14/46 (30.4 %) patients.